2022
DOI: 10.1002/asia.202200074
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Nanorod Structure‐Confined Pt@CeO2 Catalyst by an In‐Situ Encapsulation Strategy for Low‐Temperature Catalytic Oxidation of Toluene

Abstract: In this work, Pt@CeO 2 catalysts with a nanorod structure (Pt@CeO 2 À R) and a bunch structure (Pt@CeO 2 À B) were synthesized through an in-situ encapsulation strategy of Pt species in Ce-MOFs, respectively. It was discovered that the Pt@CeO 2 À R catalyst possessed the best catalytic performance for toluene catalytic combustion, and this result was mainly caused by the confinement of Pt nanoparticles in CeÀ MOFs, which was related to the chemical state of Pt species, redox ability, and the amount of active o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…To prove this, CeO 2 -Particle with similar size of 5-10 nm is synthesized and the Ce 3+ content is 30.2% (figure S7), which is also lower than that of CeO 2 -MOF. Similarly, Ma et al found the ratio of Ce 3+ in the MOF derived Pt@CeO 2 -R is higher than that of traditional supported sample [65]. In addition, Tsai prepared a broccoli-like CeO 2 from Ce-TA MOFs, which has a higher Ce 3+ content than commercial CeO 2 nanoparticle [66].…”
Section: Possible Mechanism Explanationmentioning
confidence: 93%
“…To prove this, CeO 2 -Particle with similar size of 5-10 nm is synthesized and the Ce 3+ content is 30.2% (figure S7), which is also lower than that of CeO 2 -MOF. Similarly, Ma et al found the ratio of Ce 3+ in the MOF derived Pt@CeO 2 -R is higher than that of traditional supported sample [65]. In addition, Tsai prepared a broccoli-like CeO 2 from Ce-TA MOFs, which has a higher Ce 3+ content than commercial CeO 2 nanoparticle [66].…”
Section: Possible Mechanism Explanationmentioning
confidence: 93%